2017
DOI: 10.1016/j.ocecoaman.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk assessment in a contaminated estuary: An integrated weight of evidence approach as a decision support tool

Abstract: Environmental risk assessment of complex ecosystems such as estuaries is a challenge, where innovative and integrated approaches are needed. The present work aimed at developing an innovative integrative methodology to evaluate in an impacted estuary (the Sado, in Portugal, was taken as case study), the adverse effects onto both ecosystem and human health. For the purpose, new standardized lines of evidence based on multiple quantitative data were integrated into a weight of evidence according to a best expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It has been suggested that risk assessment frameworks and decision support systems consider the genotoxicity of chemical mixtures as part of a weight of evidence approach. This has been demonstrated by the method integrating nine lines of evidence in contaminated estuaries in Portugal ( Caeiro et al, 2017 ), the policy frameworks and risk assessment tools at contaminated sites in the Netherlands ( Dagnino et al, 2008 ), and the acceptance of genotoxic tools as one of the standard monitoring strategies within the European Union Water and Marine Strategy Framework Directives ( Allan et al, 2006 ; Martins & Costa, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that risk assessment frameworks and decision support systems consider the genotoxicity of chemical mixtures as part of a weight of evidence approach. This has been demonstrated by the method integrating nine lines of evidence in contaminated estuaries in Portugal ( Caeiro et al, 2017 ), the policy frameworks and risk assessment tools at contaminated sites in the Netherlands ( Dagnino et al, 2008 ), and the acceptance of genotoxic tools as one of the standard monitoring strategies within the European Union Water and Marine Strategy Framework Directives ( Allan et al, 2006 ; Martins & Costa, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that risk assessment frameworks and decision support systems consider the genotoxicity of chemical mixtures as part of a weight of evidence approach. This has been demonstrated by the method integrating nine lines of evidence in contaminated estuaries in Portugal (Caeiro et al 2017), the policy frameworks and risk assessment tools at contaminated sites in the Netherlands (Dagnino et al 2008), and the acceptance of genotoxic tools as one of the standard monitoring strategies within the European Union Water and Marine Strategy Framework…”
Section: Discussionmentioning
confidence: 99%
“…The multiple endpoints offer more robust causeeffect relationships than, for instance, surveying biological effects or concentrations of pollutants alone (see Chapman et al 2013). In general, the outline of such strategies ranges from studies involving testing of natural waters ex situ onto surrogate crustaceans, such as Daphnia (Cruzeiro et al 2017) to multi-endpoint Best Professional Judgement approaches to address complex scenarios implicating a wide range of mixed pollutants, multiple estuarine species, in vitro testing and even epidemiology (Caeiro et al 2017). In Table 1, we highlight some of the most representative works that aimed at ERA in estuaries that are either focused on pesticides specifically or include pesticides among a large array of pollutants.…”
Section: Challenges In Environmental Risk Assessmentmentioning
confidence: 99%